MAPPING ANALYSIS OF THE ORGANIZATIONAL CULTURE BY APPLYING THE ORGANIZATIONAL CULTURE ASSESEMENT INSTRUMENT (OCAI) AT PT. BANK MUAMALAT INDONESIA BOGOR AREA - Sumardjono Jono (STIE Binaniaga, 2016)
This research has been applying a survey method of the Organizational Culture Assessment Instrument (OCAI). The researcher had been surveying to 15 potential positions, Operational Manager, Brand Manager Human Resource Manager (HRD), Marketing Manager, Secretary Asistant (SA), Operational, Public Service, Back Office, Funding Support Unit, Teller, Customer Service, Brand Internal Control (BIC), Security, General Service and Driver by implementing the quantitative and qualitative(descriptive) approaches in order to discover and to anaylize the current profile of PT Bank Muamalat Indonesia Culture, especially Bogor area and the profile of PT Bank Muamalat Indonesia in Bogor Area for the next five years. The result of the research has explained that the profile of the organizational culture (PBO) has been still applying continuously a clan organizational culture either currently or for the next five years. A clan culture is a culture profile where the organization has been still implementing mostly the clan/family relationship system which is as a particular characteristic of this organization. This organization has its own leadership style refers to as a conflict facilitator that has been facilitating a conflict or all problems happened within the organization. The criteria of the effectiveness of the system refers to a cohesive team, employees moral development, and Human Resources.Keywords : Organizational Culture Transformation, Organizational Culture Mapping, OCAI.